Does body satisfaction influence self‐esteem in adolescents' daily lives? An experience sampling study. (7th September 2015) - Fuller‐Tyszkiewicz, Matthew; McCabe, Marita; Skouteris, Helen; Richardson, Ben; Nihill, Kristy; Watson, Brittany; Solomon, Daniel
ABSTRACT: This study examined, within the context of the Contingencies of Self‐Worth model, state‐based associations between self‐esteem and body satisfaction using the experience sampling method. One hundred and forty‐four adolescent girls (mean age = 14.28 years) completed up to 6 assessments per day for one week using Palm Digital Assistants, in addition to baseline measures of trait body satisfaction and self‐esteem. Results showed considerable variation in both state‐based constructs within days, and evidence of effects of body satisfaction on self‐esteem, but not vice versa. Although these state‐based associations were small in size and weakened as the time lag between assessments increased for the sample as a whole, individual differences in the magnitude of these effects were observed and predicted by trait self‐esteem and body satisfaction. Collectively, these findings offer support for key tenets of the Contingencies of Self‐Worth model.